2013
DOI: 10.1309/ajcpdtrto2z4uexd
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Survey of Cathepsin K Immunoreactivity in Human Neoplasms

Abstract: Cathepsin K is consistently and diffusely expressed in alveolar soft part sarcoma (ASPS) and a subset of translocation renal cell carcinomas (RCCs). However, cathepsin K expression in human neoplasms has not been systematically analyzed. We constructed tissue microarrays (TMA) from a wide variety of human neoplasms, and performed cathepsin K immunohistochemistry (IHC). Only 2.7% of 1,140 carcinomas from various sites exhibited cathepsin K labeling, thus suggesting that among carcinomas, cathepsin K labeling is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…1B). In a clinical study, cathepsin K staining revealed high expression in 65% of melanomas (21). Data from normal skin is available in the databases, but because MC constitute only a small fraction (approximately 3%) of the cells in the epidermis, we did not consider these data.…”
Section: Expression Of Cathepsins In Melanoma Cellsmentioning
confidence: 99%
“…1B). In a clinical study, cathepsin K staining revealed high expression in 65% of melanomas (21). Data from normal skin is available in the databases, but because MC constitute only a small fraction (approximately 3%) of the cells in the epidermis, we did not consider these data.…”
Section: Expression Of Cathepsins In Melanoma Cellsmentioning
confidence: 99%
“…4 TFEB is a master transcriptional regulator of lysosomal biogenesis 5 and translocation carcinomas overexpress lysosomal proteases. 6 TFEB is also implicated in other functions like autophagy, 7 endocytosis, 8 exocytosis, 9 lipid metabolism, 10 the antiviral response, 11 and lysosomal calcium signaling. 12 Mice deficient for Tfeb/Tcfeb die at midgestation due to deficient placental vascularization 13 and may exhibit defects in endoderm development.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike melanoma, clear cell sarcoma has a reciprocal translocation t (12:22) resulting in the fusion of EWS RNA-binding protein 1 (EWSR1) with activating transcription factor 1 (ATF1) in more than 90% of cases. In a study performed by Zheng et al, 23 cathepsin K showed positivity in 3 of 12 cases (25%) of clear cell sarcoma (one showed focal positivity). They suggested that a diffuse staining pattern favors ASPS.…”
Section: Differential Diagnosismentioning
confidence: 91%